THE EFFECT OF SERVICE QUALITY AND SALES PROMOTION ON REPURCHASE INTENTION THROUGH CUSTOMER SATISFACTION : Study on GrabFood Customer Students in Malang City - Syah Reza Al Faisal; Agus Hermawan; Titis Shinta Dhewi (Yayasan Education and Social Center, 2022)
In service-based e-commerce companies, customer satisfaction is very important to achieve the goals of these services. This is because if the customer is not satisfied with the service that has been provided, it is possible that the customer will not be loyal and make repeated purchases of the company. With this statement, the company can measure customer satisfaction to know in detail what variables affect customer satisfaction, including service quality and sales promotion. This study aims to determine the direct or indirect effect of service quality and sales promotion on repurchase intention through customer satisfaction. This research was conducted on students at 4 different campuses in the city of Malang. The sample of this study amounted to 100 obtained by purposive sampling technique. The analysis used in the analysis using PLS (Partial Least Square). The results of this research show that the direct effect is positive and significant, while the indirect effect is also positive and significant. It is proven that service quality and sales promotion can make customers feel satisfied and make repeat purchases